Functional Characterization of Endophytic Fungal Community Associated with Oryza sativa L. and Zea mays L. - Potshangbam, Momota; Devi, S. Indira; Sahoo, Dinabandhu; Strobel, Gary A. (Frontiers in Microbiology, 2017)
In a natural ecosystem, the plant is in a symbiotic relationship with beneficial endophytes contributing huge impact on its host plant. Therefore, exploring beneficial endophytes and understanding its interaction is a prospective area of research. The present work aims to characterize the fungal endophytic communities associated with healthy maize and rice plants and to study the deterministic factors influencing plant growth and biocontrol properties against phytopathogens, viz, Pythium ultimum, Sclerotium oryzae, Rhizoctonia solani and Pyricularia oryzae. A total of 123 endophytic fungi was isolated using the culture-dependent approach from different tissue parts of the plant. Most dominating fungal endophyte associated with both the crops belong to genus Fusarium, Sarocladium, Aspergillus, and Penicillium and their occurrence was not tissue specific. The isolates were screened for in vitro plant growth promotion, stress tolerance, disease suppressive mechanisms and based on the results, each culture from both the cereal crops was selected for further study. Acremonium sp. (ENF 31) and Penicillium simplicisssum (ENF22), isolated from maize and rice respectively could potentially inhibit the growth of all the tested pathogens with 46.47±0.16 mm to 60.09±0.04mm range zone of inhibition for ENF31 and 35.48±0.14 to 62.29±0.15mm for ENF22. Both significantly produce the defensive enzymes, ENF31 could tolerate a wide range of pH from 2-12, very important criteria, for studying plant growth in different soil types, especially acidic as it is widely prevalent here, making more land unsuitable for cultivation. ENF22 grows in pH range 3-12, with 10% salt tolerating ability, another factor of consideration. Study of root colonization during 7th to 30th days of growth phase reveals that ENF31 could colonize pleasantly in rice, though a maize origin, ranging from 1.02 to 1.21 log10 CFU/g root and in maize, it steadily colonizes ranging from 0.95 to 1.18 log10 CFU, while ENF22 could colonize from 0.98 to 1.24 Log10CFU/g root in rice and 1.01 to 1.24Log10CFU/g root in maize, just the reverse observed in Acremonium sp. Therefore, both the organism has the potency of a promising Bio-resource agent, that we must definitely explore to fill the gap in the agriculture industry.